Immersive visualisation of intracardiac blood flow in virtual reality on a patient with HLHS. (8th February 2021) - Bhattacharya, S; Lin, E; Sajith, G; Munroe, L; Pushparajah, K; Schnabel, JA; Simpson, JM; Gomez, A; De Vecchi, A; Deng, S; Wheeler, G
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): NIHR i4i funded 3D Heart project Wellcome/EPSRC Centre for Medical Engineering [WT 203148/Z/16/Z] onbehalf: 3D Heart Project Background/Introduction: Virtual Reality (VR) for surgical and interventional planning in the treatment of Congenital Heart Disease (CHD) is an emerging field that has the potential to improve planning. Particularly in very complex cases, VR permits enhanced visualisation and more intuitive interaction of volumetric images, compared to traditional flat-screen visualisation tools. Blood flow is severely affected by CHD and, thus, visualisation of blood flow allows direct observation of the cardiac maladaptions for surgical planning. However, blood flow is fundamentally 3D information, and viewing and interacting with it using conventional 2D displays is suboptimal. Purpose: To demonstrate feasibility of blood flow visualisation in VR using pressure and velocity obtained from a computational fluid dynamic (CFD) simulation of the right ventricle in a patient with hypoplastic left heart syndrome (HLHS) as a proof of concept. Methods: We extend an existing VR volume rendering application to include CFD rendering functionality using the Visualization Toolkit (VTK), an established visualisation library widely used in clinical software for visualising medical imaging data. Our prototype displays the mesh outline of the segmented heart, a slicing plane showing blood pressure on the plane within the heart, and streamlines of blood flow from a spherical source region. Existing user tools were extended to enable interactive positioning, rotation and scaling of the pressure plane and streamline origin, ensuring continuity between volume rendering and CFD interaction and, thus, ease of use. We evaluated if rendering and interaction times were low enough to ensure a comfortable, interactive VR experience. Our performance benchmark is a previous study showing VR is acceptable to clinical users when rendering speed is at least 90 fps. Results: CFD simulations were successfully rendered, viewed and manipulated in VR, as shown in the Figure. Evaluating performance, we found that visualisation of the mesh and streamlines was at an acceptably high and stable frame rate, over 150fps. User interactions of moving, rotating or scaling the mesh or streamlines origin did not significantly reduce this frame rate. However, rendering the pressure slicing plane reduced frame rate by an unacceptable degree, to less than 10fps. Conclusion: Visualisation of and interaction with CFD simulation data was successfully integrated into an existing VR application. This aids in surgery and intervention planning for defects heavily relying on blood flow simulation, and lays a foundation for a platform for clinicians to test interventions in VR. Pressure plane rendering performance will require significant optimisation, potentially addressed by updating the pressure plane data separately from the main, VR rendering.